THE IMPLICATION OF THE STRATEGIES TO THE MAINTENANCE OF MEANING IN TRANSLATING NEW KING JAMES VERSION INTO INDONESIAN - Tololiu, Yunita Gloria (LITERA : Jurnal Bahasa Dan Sastra, 2020)
ABSTRACTTranslation is a process of transferring a text from a language to another. In translatinga text, the translator used strategies to transfer SL into TL. The strategy of translation is aneffective way to make the translator easier to transfer meaning. The objectives of this paper are(1) to find out the types of Biblical term occur in the New King James Version and (2) toidentify the strategies of translation that used by the translator in transferring the meaning ofSL to TL in New King James Version into Indonesian. The collected data was done by thedocumentation method. The analyzed data was done by the qualitative method anddescriptively presented. The result showed that there are types of person (5 data), place (2 data),thing (5 data), event (4 data), and action (4 data). In using the strategies of translation, thereare 4 data categorized as Direct Translation which are calque (1 data) and literal translation (3data) and there are 15 data categorized as Oblique Translation which are transposition (1 data),adaptation (11 data) and modulation (4 data).Keywords: translation, strategies of translation, biblical termABSTRAKPenerjemahan adalah proses mentransfer teks dari suatu bahasa ke bahasa yang lain.Dalam menerjemahkan teks, penerjemah menggunakan strategi untuk mentransfer BSu ke BSa.Strategi penerjemahan merupakan cara yang efektif untuk membuat penerjemah lebih mudahmentransfer arti tersebut. Tujuan dari makalah ini adalah (1) untuk mengetahui jenis-jenisistilah Alkitab yang terjadi dalam New King James Version dan (2) untuk mengidentifikasistrategi penerjemahan yang digunakan oleh penerjemah dalam mentransfer makna BSu ke BSadalam New King. Versi James dan terjemahannya dalam Bahasa Indonesia. Data yangdianalisis menggunakan metode kualitatif dan disajikan secara deskriptif. Hasil penelitianmenunjukkan bahwa ada tipe person (5 data), place (2 data), thing (5 data), event (4 data) danaction (4 data). Dalam menggunakan strategi penerjemahan, ada 4 data yang dikategorikansebagai Direct Translation yang merupakan calque (1 data) dan literal translation (3 data)dan ada 15 data yang dikategorikan sebagai Oblique Translation yang adalah transposition(1 data), adaptation (11 data) dan modulation (4 data).Kata Kunci: penerjemahan, strategi penerjemahan, istilah alkitab